Integration of the metabolome and transcriptome reveals the metabolites and genes related to nutritional and medicinal value in Coriandrum sativum - Tong WU; Shu-yan FENG; Qi-hang YANG; Preetida J BHETARIYA; Ke GONG; Chun-lin CUI; Jie SONG; Xiao-rui PING; Qiao-ying PEI; Tong YU; Xiao-ming SONG (Journal of Integrative Agriculture, 2021)
Coriandrum sativum (Coriander) or Chinese parsley is a culinary herb with multiple medicinal effects, which is widely used in cooking and traditional medicine. It is enriched with essential oils and anti-oxidant compounds with unknown significance. To explore the untapped reservoir of Coriander, we studied the transcriptome and metabolic profiles from three developmental stages. Here, we identified 10 tyrosine metabolic pathway-related genes (TMPRGs), six porphyrins and chlorophyll metabolic pathway-related genes (PCMPRGs), and five Vitamin E metabolic pathway-related genes (VEMPRGs). These genes were associated with the early development of Coriander. Our analysis suggests that these pathways are involved in the production of critical phenolic metabolites. Furthermore, we constructed the interaction network between these pathway-related genes and transcription factors (TFs), which supported the regulatory pathways for phenolic metabolites. Interestingly, we identified several nutritional or medicinally relevant metabolites, including 59 phenols, two polyamines, 12 alkaloids, and one terpenoid. The higher concentrations of metabolites were from caffeic acid, agmatine, and its derivatives. We found higher levels of caffeic acid and agmatine at 30 days compared to 60 or 90 days. This study provides evidence to stimulate further investigation of the role of these metabolites in medicinal and nutritional research.